The Role of Project-Based Learning in Developing Professional Culture of Future Art Teachers - Esanova Lobar Kulmurotovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores how project-based learning (PBL) contributes to the development of professional culture among future art teachers. It highlights pedagogical methods that integrate creative problem-solving, critical thinking, and cultural awareness. The study emphasizes the importance of combining cognitive, emotional, and aesthetic components to foster artistic competence and professional readiness in students.